Internalization of Islamic Values through SIRAJA School Culture in the Formation of Students' Religious Character - Mirra Ardiani Zhafira; Munawar Rahmat; Mohammad Rindu Fajar Islamy (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
The moral degradation of Indonesian adolescents is a persistent problem that cannot be resolved solely through cognitive-based Islamic religious education (PAI). This study aims to analyze the internalization process of Islamic values through SIRAJA school culture, identify the values embedded within it, explain its role in forming students' religious character, and identify the factors influencing the process. Employing a qualitative single case study design, data were gathered through in-depth interviews with 14 informants comprising educators, students, and school administrators, as well as observation and documentation, analyzed using source triangulation. Results show that internalization proceeds through four successive stages: value transmission, habituation, exemplary modeling, and reinforcement. SIRAJA's six pillars (Polite, Innovative, Resilient, Adaptive, Honest, and Trust) are integrated across all subjects and school activities, contributing to the formation of a value ecosystem that extends the scope of the formal curriculum. Success is supported by structured institutional planning, teacher modeling, and a conducive school environment. This study contributes to Islamic education scholarship by demonstrating that value internalization becomes more systematic when school culture is institutionally constructed with a self-designed identity, named pillars, and a sustainable evaluation mechanism rather than relying solely on generic religious practices.